LSCS notes audit in a tertiary referral centre of Uttar Pradesh, India - Pandey, Uma; Naqvi, Asna; Dwivedi, Shipra; Gupta, Shefali (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Obstetrics is a very litigious branch as the nature of job is highly pressured and it deals with two lives a mother and baby/babies. There are situations where there are no mistakes but there is no ‘documentation’ of due to high turnover of labouring women which leads to difficulty in dealing with medico legal cases. It is due to this reasons we decided to do an audit of our Caesarean section operative notes. Methods: We planned to audit the quality of caesarean section documentation in a University teaching hospital of North India at Banaras Hindu University. The study involved 57 case notes from the first January 2015 to 24 February 2015. The proforma was filled by residents within 72 hours of the operative procedure. Results: Date of Lower Segment Caesarean Section (LSCS) was from 01.01.2015 to 24.02.2015 and total of 57 case notes were included in this study. Hospital number, date of LSCS and time of LSCS was written in the operative notes of all patients. Written consent was also taken from patient party in all cases of LSCS. There were 6 cases of General anaesthesia (GA) in which two GA were preceded by spinal which had failed. Hand writing was legible in all records and was written by second year residents and signed. Conclusions: The above audit done at University teaching hospital of North India at Banaras Hindu University which included 57 notes shows a very high quality of record maintenance. This audit was conducted while the Obstetric team was aware that audit of record keeping is taking place. It is difficult to ascertain whether such a high level of record maintenance is a true reflection or a Hawthorne effect.